Experimental data for creep and dynamic mechanical properties of polycarbonate and polycarbonate/acrylonitrile-butadiene-styrene - Quanyi Mu (Data in Brief, 2022)
The data available in this article presents the tensile creep behaviors and dynamic mechanical properties of polycarbonate (PC) and the alloy of polycarbonate/acrylonitrile-butadiene-styrene (PC/ABS). Optical method in conjunction with a universal testing machine was used to get the creep deformation, and finally obtained the creep strain-time curves at different stress levels. The tensile creep stress levels for PC were 52 MPa, 50 MPa, 49 MPa, 48 MPa, 47 MPa, 41 MPa, and 47 MPa, 45 MPa, 43 MPa, 41 MPa, 39 MPa, 30 MPa for PC/ABS. Furthermore, the microstructural images of the creep fracture surface of PC and PC/ABS at different stress levels were obtained by using scanning electron microscope (SEM). Finally, the dynamic mechanical raw data of PC and PC/ABS were tested using dynamic mechanical analysis (DMA), and the dynamic mechanical properties of PC/ABS at three frequencies (0.1 Hz, 1 Hz and 10 Hz) were presented. The creep data can be reused to predict the long-term creep behavior of PC and PC/ABS, either by modeling predictions or by using the superposition principle to construct a long-term creep master curve. The SEM images and dynamic mechanical data can facilitate the investigating of the viscoelastic mechanism of PC and PC/ABS. These data can also be reused for comparison with PC and PC/ABS manufactured using other methods, such as 3D printed or recycled.